The Black period : on personhood, race, and origin - Geter, Hafizah, 1984- (Random House, 2022)
"Hafizah Augustus Geter disrupts the myths of America's origins and contemporary America through her experiences as the queer Nigerian-born daughter of a Muslim Nigerian woman and a Black American man from a Southern Baptist family in Jim Crow Alabama. A unique combination of gripping memoir and Afrofuturist thought, The Black Period follows Hafizah on a journey that tells her at every turn she's not worthy. At the same time, she manages to sidestep shame, confront disability, embrace forgiveness, and emerge from the erasures America imposes to exist proudly and unabashedly as herself. Penetrative and heartening, The Black Period captures a world brimming with potential, art, music, hope, and love despite the lasting effects of white supremacy"--